[LEGISLATION RE: DISCRIMINATION IN HIRING BASED ON OFF-THE-JOB ACTIVITIES] - SANATOR JONES (Tufts Archival Research Center, 2007)
Marginalia; Proposal for a bill prohibiting unfair employment hiring practices in the state of Florida. Strives to eliminate hiring discrimination based on participation in lawful activities during non-working hours.